Kepemimpinan Transformasional Dan Kultur Inovasi: Strategi Digital Academic Leadership Dalam Menghadapi Era Society 5.0 - Dewi, Ratna Kusuma (Postgraduate of Jayabaya University, 2025)
This study examines the role of transformational leadership in strengthening Digital Academic Leadership (DAL) and fostering an innovation culture within higher education institutions in response to the demands of Society 5.0. Using a narrative conceptual literature review, this research explores how the four pillars of transformational leadership (idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration) contribute to the development of human-centered digital academic leadership. The analysis demonstrates that transformational leadership is essential for shaping a transformative digital vision, empowering digital human resources, and embedding humanistic values in digital governance. Furthermore, the study highlights that the integration of transformational leadership principles with digital competencies forms a strategic foundation for creating an adaptive, collaborative, and sustainable innovation culture in higher education.